Anatomy of Vice President analysis of the 2018 news coverage of Vice President Maria leonor "Leni" Robredo in the six major Philippine broadsheets - Gagua, Frances Jade Verar 1998-
Vice President Robredo is a controversial political figure not just because of her position but more so due to her political affiliations. In 2018 alone she faced an electoral dispute, weathered the criticism and scrutiny of Presidential Rodrigo Duterte, and denied countless allegations which include claims of a drug trade in her hometown, rumors of a romantic relationship with a married politician, and accusations of ties to an ouster plot against Duterte. The thesis seeks to analyze how the six major Philippine broadsheets portrayed Robredo in 2018. Using the framing theory, the research studied six issues to determine whether the newspaper coverage of Robredo is positive, negative, or neutral; and more importantly, if the six broadsheets exhibited gender bias and political bias in their reportage. The study found that Robredo was portrayed negatively in majority of the issues. Overall, Daily Tribune, manila Standard, and The Manila Times portrayed Robredo negatively; Philippine Star portrayed Robredo neutral-negatively; Manila Bulletin portrayed Robredo neutral-positively; and Philippine Daily Inquirer portrayed Robredo positively. Little gender bias was exhibited in the articles; and each publication's political bias follows the tone of their coverage.